Dynamics of Indian Foreign Exchange Market Efficiency : An Adaptive Market Hypothesis Approach - Khuntia, Sashikanta; Pattanayak, J. K. (Indian Journal of Finance, 2017)
Adaptive market hypothesis (AMH), a recent evolution in the field of finance, advocates that market efficiency is a time-variant element. In the present study, we empirically verified the time-varying degrees of market efficiency as per the propositions of AMH in the Indian foreign exchange market, which is assumed to provide an evolutionary alternative to the efficient market hypothesis (EMH).Â For the purpose, we used daily bilateral exchange rate between Indian rupee/United States dollar from January 1999 to December 2015. Statistical tests with linear and nonlinear approaches and better power properties unlike previous studies were used to trace the market efficiency. All tests employed unanimously supported time-varying nature of efficiency in foreign exchange returns, which adhere to the premise of AMH. The findings of the study confirmed market efficiency as an element which evolves with different market conditions, and thereby suggested for adoption of active portfolio management strategies for currency traders.